Is leigen fünff Perg in welschen Landt.: Eine Topographie der Pilgerwege von Deutschland nach Santiago in Spanien aus dem 15. Jahrhundert - Hard, Gerhard (ERDKUNDE, 1965)
A German pilgrims’ hymn (von sant Jacob) embodies a corrupted and in part nearly unrecognizable description of the pilgrims’ ways to Santiago in Galicia. The paper attempts firstly to outline the value of the via Jacobitanae for the historical geography of Middle and Western Europe and secondly, with the aid of a more comprehensive source material, to analyse the topographical and historical geographical contents of the hymn. Such an analysis seems particularly rewarding as one may assume that until modern times the geographical concept of Wes tern Europe was amongst the populace of Middle Europe on the whole derived from the Jacob’s pilgrimage and the holy routeways used by it. Some places on these routes even assumed symbolic importance. The analysis inter alia shows that in this hymn several different routes have become linked and mixed up. The routes which it contains and which can be reconstructed present partly different historical stages of the Jacob’s pilgrims’ ways. It can further more be shown that the German pilgrims coined their own German place names which differed equally from the local names as from the toponymy used in the itineraria of the English pilgrims and Romance peoples.